Jealousy in context : the social implications of emotions in the Hebrew Bible - Villareal, Erin, 1986- (University park: Eisenbrauns, 2022)
"Evaluates the socioliterary context of jealousy in Biblical Hebrew"--
Includes bibliographical references (pages 179-199) and indexes.
Keywords: Jealousy in the Bible; Jealousy -- Religious aspects -- Judaism